Matching Diabetes and Alcoholism: Oxidative Stress, Inflammation, and Neurogenesis Are Commonly Involved - Jorge M. Barcia; Miguel Flores-Bellver; Maria Muriach; Javier Sancho-Pelluz; Daniel Lopez-Malo; Alba C. Urdaneta; Natalia Martinez-Gil; Sandra Atienzar-Aroca; Francisco J. Romero (Mediators of Inflammation)
Diabetes and alcohol misuse are two of the major challenges in health systems worldwide. These two diseases finally affect several organs and systems including the central nervous system. Hippocampus is one of the most relevant structures due to neurogenesis and memory-related processing among other functions. The present review focuses on the common profile of diabetes and ethanol exposure in terms of oxidative stress and proinflammatory and prosurvival recruiting transcription factors affecting hippocampal neurogenesis. Some aspects around antioxidant strategies are also included. As a global conclusion, the present review points out some common hits on both diseases giving support to the relations between alcohol intake and diabetes.